Trust Issues that Create Threats for Cyber Attacks in Cloud Computing - Khorshed, M. T.; Ali, A. B. M. S.; Wasimi, S. A. (2011 IEEE 17th International Conference on Parallel and Distributed Systems, 2011)
The research contribution in this paper is twofold. First, an investigative survey on cloud computing is conducted with the main focus on gaps that is slowing down cloud adoption as well as reviewing the threat remediation challenges. Next, some thoughts are constructed on novel approaches to address some of the widely discussed attack types using machine learning techniques. Such thoughts captured through a series of experiments are expected to give researchers, cloud providers and their customers' additional insight and tools to proactively protect themselves from known or perhaps even unknown security issues that follow the same patterns.